Mucilage Facilitates Nutrient Diffusion in the Drying Rhizosphere. Issue 1 (8th August 2019) - Zarebanadkouki, Mohsen; Fink, Theresa; Benard, Pascal; Banfield, Callum C.
Abstract : Core Ideas: Our aim was to test whether mucilage promotes diffusion of nutrients in dry soil. Mucilage favors transport of nutrients in drying soil and their uptake by plant. Mucilage increases the soil moisture in the rhizosphere as soil dries. Mucilage maintains the connectivity of liquid phase in the rhizosphere as soil dries. Despite detailed investigations of its distinct biochemical properties and their effects on the availability of nutrients for plants, the biophysical aspects of the rhizosphere, particularly the effect of mucilage on the transport of water and nutrients, are poorly understood. The aim of this study was to investigate the effect of mucilage on the diffusion of nutrients and consequently their transport through the rhizosphere into the plant roots. Phosphor imaging technique determined the temporospatial distribution of 137 Cs in a model rhizosphere (a sandy soil mixed with chia seed ( Salvia hispanica L) mucilage. The observed profiles of activities were used to estimate the diffusion coefficient of K in soils. A diffusion–convection equation was numerically solved to predict the transport of K and its uptake by a single plant root in drying soil. The results suggest that mucilage (i) keeps the rhizosphere wet and (ii) maintains the connectivity of the liquid phase in drying soil. In these ways, mucilage moderates the drop in diffusive transport. The modeling results showed that the presence of mucilage in the rhizosphere (i) prevents depletion of nutrients in soils with a low nutrient concentration in the soil solution and (ii) delays the risk of nutrient and/or salt accumulation in the vicinity of the root in soils with a high concentration nutrient and/or salt the soil solution. In conclusion, mucilage appears to mitigate the risk of nutrient deficiency and salinity stress as it enhances the diffusive transport in drying soil. In this way, mucilage may favor the transport of nutrients within the rhizosphere and their uptake by plant roots in drying soil.